Effect of Exercise Modality on Heart Rate Variability in Adults: A Systematic Review and Network Meta-Analysis - Faming Yang; Ying Ma; Shuangyan Liang; Yali Shi; Chen Wang (Reviews in Cardiovascular Medicine, 2024)
Background: The purpose of this study was to use a network meta-analysis (NMA) to compare the effects of aerobic training (AT), resistance training (RT), combined training (CBT), and high-intensity interval training (HIIT) on adult heart rate variability (HRV). Methods: We searched PubMed, the Cochrane Library, Embase, the Web of Science, Wanfang Data, and the China National Knowledge Infrastructure to identify randomized controlled trials on the effects of exercise on HRV in adults. The search was conducted from the outset of these databases to April 2023. Two reviewers independently screened the retrieved articles, extracted raw data from the relevant studies, and assessed the possible risk of bias in the included studies. Results: The NMA showed that HIIT had the greatest effect on the low-frequency (LF) power/high-frequency (HF) power ratio, standard deviation of normal–normal intervals (SDNN), and root mean square of successive differences between adjacent normal-to-normal intervals (RMSSD) (surface under the cumulative ranking curve (SUCRA) = 99.75%, 98.7%, and 84.9%); CBT had the greatest effect on the LF power (SUCRA = 66.3%); RT had the greatest effect on the HF power (SUCRA = 72.5%). Conclusions: Our NMA and SUCRA ranking results suggest that in adults, HIIT is the most effective exercise modality in improving the SDNN, RMSSD, and LF/HF power ratio; RT for the HF power; CBT for the LF power. Any NMA conducted in the future must fully explore the effects of different exercise modalities on HRV in adult subgroups of different ages and genders. Systematic Review Registration: https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=424054, identifier: CRD42023424054.